1964
DOI: 10.1136/jnnp.27.2.96
|View full text |Cite
|
Sign up to set email alerts
|

Serum enzyme studies in muscle disease: Part II Serum creatine kinase activity in muscular dystrophy and in other myopathic and neuropathic disorders

Abstract: It has been established that the levels of certain enzymes are elevated in the serum of patients suffering from muscular dystrophy. Previous studies

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
41
0
2

Year Published

1965
1965
1981
1981

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(44 citation statements)
references
References 12 publications
(3 reference statements)
1
41
0
2
Order By: Relevance
“…A much smaller increase is found in the other forms of muscular dys trophy (limb-girdle type, facioscapulohumeral type, ocular type, oculo-pharingeal and distal types). Even a smaller increase is found in dystrophia myotonica [13,16,24,27,29,36,39]. The very high values found in the pre-clinical and early stages of Duchenne type and to a lesser extent in the Becker type and limb-girdle type are not main-…”
Section: Introductionmentioning
confidence: 86%
“…A much smaller increase is found in the other forms of muscular dys trophy (limb-girdle type, facioscapulohumeral type, ocular type, oculo-pharingeal and distal types). Even a smaller increase is found in dystrophia myotonica [13,16,24,27,29,36,39]. The very high values found in the pre-clinical and early stages of Duchenne type and to a lesser extent in the Becker type and limb-girdle type are not main-…”
Section: Introductionmentioning
confidence: 86%
“…was 58 units per ml. per minute, andtheserumcreatine kinase level 12-6 unitsaccording to the method of Pearce, Pennington, and Walton (1964) LIGHT MICROSCOPY The muscle fibres were everywhere embedded in dense connective tissue; they showed great diversity of size from considerable hypertrophy to extreme atrophy (Fig. 4).…”
mentioning
confidence: 99%
“…The increase in Asp [3] was not statistically significant, nor were the differences in Thr [1 ] and Arg [1]. The remaining nine amino acids found in dystrophic myosin differed by less than one residue and in each case by ' 2.5 % of normal.…”
mentioning
confidence: 90%
“…Biochemical studies of hereditary human and animal progressive muscular dystrophy have revealed a variety of abnormalities such as elevated serum enzymes and lowered muscle enzyme activity, increased creatine excretion, and lowered muscle potassium content, which have been recently reviewed (1,2). These changes are, however, generally considered to be secondary to muscle destruction (2)(3)(4). A muscle protein abnormality has been suggested in recent studies by Kruh, Dreyfus, Schapira, and Gey (5), and by Simon, Gross, and Lessell (6), showing an increased rate of muscle protein catabolism in hereditary dystrophy of mice.…”
mentioning
confidence: 95%